2015
DOI: 10.1002/agr.21429
|View full text |Cite
|
Sign up to set email alerts
|

Cooperatives’ Organizational Restructuring, Strategic Attributes, and Performance: The Case of Agribusiness Cooperatives in Greece

Abstract: We develop a classification of traditional versus restructured cooperative organizational attributes based on an inductive approach. Using this classification and integrating concepts from the business literature (i.e., market and brand orientation), we hypothesize three types of relationships: (a) the influence of organizational attributes, i.e., ownership, control and cost/benefit allocation, on organizational performance; (b) the influence of strategic, i.e., market and brand orientation, attributes on orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
3
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 77 publications
(151 reference statements)
0
79
3
13
Order By: Relevance
“…Empirical evidence for the contribution of market orientation on the performance of the cooperative is very scarce compared with IOFs (Benos et al, 2016). In particular, information on the relationship between market orientation and performance of agricultural cooperatives in the D&E context is very scant.…”
Section: Market Orientation and Cooperativesmentioning
confidence: 99%
See 4 more Smart Citations
“…Empirical evidence for the contribution of market orientation on the performance of the cooperative is very scarce compared with IOFs (Benos et al, 2016). In particular, information on the relationship between market orientation and performance of agricultural cooperatives in the D&E context is very scant.…”
Section: Market Orientation and Cooperativesmentioning
confidence: 99%
“…Prior studies indicate that strengthening of customer orientation has been claimed to be essential for the success of marketing cooperatives (Bijman, 2010). Benos et al (2016) reported the positive influence of cooperative organisational attributes on the implementation of market orientation. They also found the positive influence of market orientation on the performance of the cooperative (sales volume, new market entry and market share).…”
Section: Market Orientation and Cooperativesmentioning
confidence: 99%
See 3 more Smart Citations